2019
DOI: 10.1108/hff-05-2019-0376
|View full text |Cite
|
Sign up to set email alerts
|

Numerical heat flow visualization analysis on enhanced thermal processing for various shapes of containers during thermal convection

Abstract: Purpose The purpose of this paper is to study thermal (natural) convection in nine different containers involving the same area (area= 1 sq. unit) and identical heat input at the bottom wall (isothermal/sinusoidal heating). Containers are categorized into three classes based on geometric configurations [Class 1 (square, tilted square and parallelogram), Class 2 (trapezoidal type 1, trapezoidal type 2 and triangle) and Class 3 (convex, concave and triangle with curved hypotenuse)]. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…A comprehensive review of the fundamental aspects of thermal convection in curved geometries and surfaces in the presence of porous media and nanofluids has been reported by Shenoy et al (2016). To understand the thermo-fluid phenomena, many researchers have studied the thermal convective phenomena in different geometries adopting curved, corrugated, sinusoidal, irregular or other wavy surfaces considering coupled multiphysical situations (Dalal, and Das, 2006; Abu-Nada and Oztop, 2011; Rahimi et al , 2018; Manna et al , 2019; Lukose and Basak, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of the fundamental aspects of thermal convection in curved geometries and surfaces in the presence of porous media and nanofluids has been reported by Shenoy et al (2016). To understand the thermo-fluid phenomena, many researchers have studied the thermal convective phenomena in different geometries adopting curved, corrugated, sinusoidal, irregular or other wavy surfaces considering coupled multiphysical situations (Dalal, and Das, 2006; Abu-Nada and Oztop, 2011; Rahimi et al , 2018; Manna et al , 2019; Lukose and Basak, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The state of the art of natural convection numerical studies, in the most diverse applications and methodologies of modeling and solution, is broadly represented by the references (Salari et al , 2017) in the three-dimensional study of turbulent/transitional natural convection with different turbulence/transition models in trapezoidal enclosures (Dash and Dash, 2020). In the analysis of conjugate heat transfer by natural convection and thermal radiation in a horizontal cylinder that is suspended in the air; (Lukose and Basak, 2020) in the study of natural convection through the Galerkin finite element method in nine different shapes of containers, with the same surface area and identical isothermal heat input at the bottom wall; (Henniche and Korichi, 2020) in the study and numerical simulation (using the software OpenFOAM®) of enhanced mixed convection heat transfer in a vertical channel with staggered inclined baffles; Raizah (2020) in the application of the ISPH method for the study of natural convection with copper-water nanofluid inside cavities with cross blades or circular cylinder cylinder; Alshomrani et al (2020) in the three-dimensional study of the influence of different locations of cooler and the tilting angles of a cavity on natural convection heat transfer in a laminar regime; Aghighi et al (2020) in obtaining solutions, through the Galerkin’s weighted residual finite element method, of the natural convection of Casson fluid in a square enclosure, under conditions of differentially heated side walls; Sasidharan and Dutta (2020) in the study of the thermal performance of a hybrid tubular and cavity solar thermal receiver; Ullah et al (2021) in the two-dimensional study of natural convection of micropolar nanofluid in a rectangular vertical container, heated on the lower wall to generate the internal flow; Lukose and Basak (2021) in the extensive literature review on the mixed convection and the proposition of 10 unified models in different physical–numerical conditions; and Nishad et al (2021) in the two-dimensional study of natural convection inside a wavy enclosure with Cu-water nanofluid under magnetic field and using the element-free Galerkin method (EFGM) with parallel algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…GFEM had been used extensively in earlier studies for CFD simulations (Basak et al , 2006; Anandalakshmi and Basak, 2015; Biswal and Basak, 2018; Das et al , 2019; Lukose and Basak, 2019; Rafiei et al , 2019). The current work employs GFEM to solve equations (7)–(9) with velocity and different thermal boundary conditions at the walls (equation (10)).…”
Section: Model Formulation Numerical Methodology Finite Element Logistics and Post-processingmentioning
confidence: 99%
“…Earlier works in literature concluded that fluid flow during natural convection is mainly dependent on the dimensionless parameters, Ra and Pr . However, a recent work (Lukose and Basak, 2019) established that in addition to the dimensionless parameters, Ra and Pr , the shape of containers also plays an important role on the fluid flow, energy flow and thermal distribution during natural convection to achieve enhanced thermal processing. In contrast to the earlier works on entropy generation (as discussed in the previous paragraphs), the role of straight wall (square, triangle, rhombic, trapezoidal) vs curved wall (convex, concave, triangle with curved hypotenuse) on entropy generation due to fluid friction and heat transfer with identical area and heat input during natural convection within various shapes of configurations is yet to appear in literature.…”
Section: Introductionmentioning
confidence: 99%